2002
DOI: 10.1093/gerona/57.9.b344
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Reflex Stiffness During Unperceived Perturbation of Standing in Elderly Subjects

Abstract: Postural reflex activity during unperceived perturbation of standing was investigated in 38 elderly subjects (70-96 years old) and 10 younger adults (19-48 years old), and it was related in the elderly group to a history of unexplained falling in the 12 months prior to testing. Ankle torque (T) and ankle angle (A) were recorded during unperceived forward pulls to obtain the ankle stiffness (DeltaT/DeltaA), providing a measure of postural reflex activity at the ankle. Elderly nonfallers and younger adults had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 14 publications
3
40
0
1
Order By: Relevance
“…Schmitt and Rudolph (45) reported on 20 patients with medial knee OA and found that higher knee muscle co-contraction was associated with greater selfreport knee instability, an important multivariate predictor of functional limitations (46), and the authors concluded that that the co-contraction strategy may be detrimental to both knee cartilage integrity and physical function. Also, biomechanical studies (33,47) have shown that individuals with increased ankle stiffness during standing were unable to adequately counteract rapid external perturbations and that postural ankle stiffness during standing was greater in elderly fallers than in nonfallers (48). Granted, we acknowledged that our explanations are speculative and additional studies are needed to test these possibilities; however, our results suggest that the interpretation of standing COP displacement measures in patients with knee OA is certainly less straightforward than previously assumed.…”
mentioning
confidence: 67%
“…Schmitt and Rudolph (45) reported on 20 patients with medial knee OA and found that higher knee muscle co-contraction was associated with greater selfreport knee instability, an important multivariate predictor of functional limitations (46), and the authors concluded that that the co-contraction strategy may be detrimental to both knee cartilage integrity and physical function. Also, biomechanical studies (33,47) have shown that individuals with increased ankle stiffness during standing were unable to adequately counteract rapid external perturbations and that postural ankle stiffness during standing was greater in elderly fallers than in nonfallers (48). Granted, we acknowledged that our explanations are speculative and additional studies are needed to test these possibilities; however, our results suggest that the interpretation of standing COP displacement measures in patients with knee OA is certainly less straightforward than previously assumed.…”
mentioning
confidence: 67%
“…Although higher co-contraction has been shown during perturbation studies in older adults who are known fallers (Ho and Bendrups 2002), it is unknown whether increased ankle co-contraction during static balance challenges is predictive of increased fall risk. Previous work has not investigated the relationships between muscle activation strategies during static balance challenges and performance on dynamic clinical assessment tools designed to assess fall risk.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that one out of three adults over the age of 65 years will fall at least once each year, and half of those will experience multiple falls (Trombetti et al 2010;Pereira et al 2008;Stevens et al 2006). Multiple studies have shown older adults to have higher levels of muscle co-contraction than their younger counterparts during balance challenges (Hortobogyi et al 2009;Chu et al 2009;Benjuya et al 2004) and elevated muscle co-contraction has also been associated with a history of falling (Ho and Bendrups 2002). Co-contraction results in stiffening of the joint, and increased joint stiffness is considered to be a compensatory strategy when faced with balance challenges (Cenciarini et al 2009;Reynolds 2010;Allum et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…단지지기 동안의 하지에 적용되는 제어는 관절강성(joint stiffness)으로 나타낼 수 있으며 관절강성은 단위 각 변위 당 모멘트로써 회전 저항(K ang = ∆M/∆θ)을 나타낸다 (Ho & Bendrups, 2002;Buzzi, Stergiou, Kurz, Hageman & Heidel, 2003;Liu & Lockhart, 2009;Lockhart, Woldstad & Smith, 2003). 이 척도는 불안전한 보행패턴의 지표 (indicator)이며 낙상의 원인이기도 하다 (Gehlesen & Whaley, 1990).…”
unclassified